2012
DOI: 10.1016/j.jnutbio.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of chromium in alleviating insulin resistance

Abstract: Type 2 diabetes is often associated with obesity, dyslipidemia, and cardiovascular anomalies and is a major health problem approaching global epidemic proportions. Insulin resistance, a prediabetic condition, precedes the onset of frank type 2 diabetes and offers potential avenues for early intervention to treat the disease. Although lifestyle modifications and exercise can reduce the incidence of diabetes, compliance has proved to be difficult, warranting pharmacological interventions. However, most of the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
98
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(110 citation statements)
references
References 88 publications
6
98
1
5
Order By: Relevance
“…However, it has also been documented that there exists compensatory increase in the intestinal absorptionof chromium in diabetes (Jeejeebhoy et al, 1977) and coupled with the use of dietary supplementation as was reported in this study (17.5%), could account for the higher plasma levels of chromium amongst the diabetics than that of the healthy subjects.Although it may be difficult to explicitlyexplain the basis of the findings of studies such as ours, the fact of the central role of chromium in enhancing insulin binding and signaling, modulation of insulin receptor number and overall enhances β-cell sensitivity is not in doubt (Hua et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, it has also been documented that there exists compensatory increase in the intestinal absorptionof chromium in diabetes (Jeejeebhoy et al, 1977) and coupled with the use of dietary supplementation as was reported in this study (17.5%), could account for the higher plasma levels of chromium amongst the diabetics than that of the healthy subjects.Although it may be difficult to explicitlyexplain the basis of the findings of studies such as ours, the fact of the central role of chromium in enhancing insulin binding and signaling, modulation of insulin receptor number and overall enhances β-cell sensitivity is not in doubt (Hua et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…However it is important to state that factors such as the analytical tools employed to assess blood levels of chromium, the influence of antidiabetic drugs to which the subjects were already on and the fact that these clinical studies were conducted in subjects with full-blown diabetes and not in pre-diabetic patients have been suggested as the basis for divergent findings in many studies (Hua, 2012). It is likely that chromium may be augmenting insulin actions in pre-diabetic patients (Hua, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of trivalent chromium in type 2 diabetic patients (especially insulin resistant) has become more common because its mechanism of action for anti-hyperglycemic effect is well explained at molecular level [48,49] and it has been found successful in clinical trials [50]. In addition to alleviating insulin resistance, the potential effect of chromium in regulating oxidative stress and inflammation has been addressed [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that supplemental chromium did not affect rectal temperature after challenge with infectious bovine rhinotracheitis virus in steers. In a succinct review by Hua et al (2012), the potential mechanisms driving chromium's effect on improving insulin resistance are explored, and it is noted that recent studies have found chromium to improve the actions of insulin and the insulin-signalling pathway while inhibiting downregulators of insulin signalling.…”
Section: Betainementioning
confidence: 99%